Parsana Health Centre : nurturing a healthy lifestyle - Thomas, Sujo, (SAGE Knowledge. Cases., 2017)
The Indian fitness industry still reflects tremendous growth potential. About 60% of the organized fitness centres were concentrated in the top eight Indian cities - Delhi, Mumbai, Bengaluru, Chennai, Kolkata, Pune, Hyderabad and Ahmedabad. Parsana Health Centre Private Limited, one of the pioneers of the organized fitness industry in the city of Ahmedabad, has been actively engaged in inculcating, nurturing and promoting a healthy lifestyle to the general public through fitness regimes over the last two decades. The owners, the Parsana brothers were well aware of the heavy competition mushrooming in the city fighting for a larger portion of the market share. They had to cut down the number of centres to eight from 13, having been drastically affected by the competition along with the innovative and creative new entrepreneurial strain, making survival and sustenance difficult. The brothers had to set their priorities right, in order to discover the best strategy for growth. They were evaluating the business model against the existing business opportunities. Their entrepreneurial journey was getting complex with a plethora of challenges in the existing competitive landscape and thereby they had to put together an appropriate promotional and positioning strategy in view of the long term objectives.